Advances in the study of myeloid-derived suppressor cells in infectious lung diseases - Zhang, Meng-Nan; Yuan, Yu-Lai; Ao, Su-Hua (Frontiers in Immunology, 2023)
Myeloid-derived suppressor cells (MDSCs) are a heterogeneous population of immature cells capable of inhibiting T-cell responses. MDSCs have a crucial role in the regulation of the immune response of the body to pathogens, especially in inflammatory response and pathogenesis during anti-infection. Pathogens such as bacteria and viruses use MDSCs as their infectious targets, and even some pathogens may exploit the inhibitory activity of MDSCs to enhance pathogen persistence and chronic infection of the host. Recent researches have revealed the pathogenic significance of MDSCs in pathogens such as bacteria and viruses, despite the fact that the majority of studies on MDSCs have focused on tumor immune evasion. With the increased prevalence of viral respiratory infections, the resurgence of classical tuberculosis, and the advent of medication resistance in common bacterial pneumonia, research on MDSCs in these illnesses is intensifying. The purpose of this work is to provide new avenues for treatment approaches to pulmonary infectious disorders by outlining the mechanism of action of MDSCs as a biomarker and therapeutic target in pulmonary infectious diseases.